Povratak duha evropskog humanizma / The Return of the Spirit of European Humanism - Jašarević, Almir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
This text is a review of a book by Rob Riemen: The Eternal Return of Fascism, published by Dereta, Belgrade, 2019, (with original title „DE EEUWIGE TERUGKEER VAN HET FASCISME DE TERUGKEER VAN EUROPA: HAAR TRANEN; DADEN EN DROMEN, Nederlands letterenfonds – Dutch Foundation for Literature, 2017).